2018
DOI: 10.1089/jwh.2017.6667
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Reminders on Papanicolaou Test Completion for High-Risk Patients Identified by a Clinical Decision Support System

Abstract: Background A clinical decision support system (CDSS) for cervical cancer screening identifies patients due for routine cervical cancer screening. Yet, high-risk patients who require more frequent screening or earlier follow-up to address past abnormal results are not identified. We aimed to assess the effect of a complex CDSS, incorporating national guidelines for high-risk patient screening and abnormal result management, its implementation to identify patients overdue for testing, and the outcome of sending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Supporting evidence supports our findings that clinicians lack systems to support identification of patients who are due for cervical screening and follow-up [ 63 ]. Patient reminders in the form of letters, text messages, using mobile applications are strategies that have been found to increase cervical cancer screening and follow-up rates [ 64 66 ]. Provision of communication tools alone is insufficient to overcoming barriers to communicating.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting evidence supports our findings that clinicians lack systems to support identification of patients who are due for cervical screening and follow-up [ 63 ]. Patient reminders in the form of letters, text messages, using mobile applications are strategies that have been found to increase cervical cancer screening and follow-up rates [ 64 66 ]. Provision of communication tools alone is insufficient to overcoming barriers to communicating.…”
Section: Discussionmentioning
confidence: 99%
“…These include: 1) Aim to have staff members that speak the patient's preferred language, 2) Providers set clear expectations with patients about the format of the colposcopy clinic, 3) Providers aim to improve consistency, following patients longitudinally when possible, and reminding patients; we keep a thorough electronic medical record to ensure appropriate care, 4) Use of electronic, automated systems that can identify patients in need of more frequent follow-up, and 5) Incorporation of telephone and electronic reminders. 11,24 Previous studies have shown that racially and ethnically diverse patient navigators can also be particularly useful in helping underserved patients successfully follow up for health care appointments; however, not all clinics have access to these resources. 3,25 Using the major themes and feedback that emerged during patient interviews, we collaborated with the Patient-Activated Learning System (PALS, PALSforHealth.com) to create a web-based educational intervention that intends to address the major knowledge gaps demonstrated among our participants.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study on patients with colon cancer, the CDSS improved guideline-adherent surveillance recommendations (77.4 vs. 84.6%; P < 0.001) [60]. Likewise, a CDSS for cervical cancer screening identified high-risk women due for cervical cancer testing beyond routine screening intervals and significantly increased the completion rate of recommended follow-up tests when compared with a historical control group (3.3– 23.7%; P < 0.001) [61]. CDSSs further contributed to the guideline-compliant selection of patients for imaging examinations in low-risk prostate cancer [62] and hepatocellular carcinoma [63].…”
Section: Evidence: Clinical Decision-support System Usage Increases G...mentioning
confidence: 91%